2012
DOI: 10.1063/1.4707097
|View full text |Cite
|
Sign up to set email alerts
|

Consideration of sub-cooled LN2 circulation system for HTS power machines

Abstract: Articles you may be interested inSub-cooled liquid nitrogen cryogenic system with neon turbo-refrigerator for HTS power equipment AIP Conf. ABSTRACTWe consider a sub-cooled liquid nitrogen (LN) circulation system for HTS power equipment. The planned circulation system consists of a sub-cool heat exchanger (subcooler) and a circulation pump. The sub-cooler will be connected to a neon turbo-Brayton cycle refrigerator with a cooling power of 2 kW at 65 K. Sub-cooled LN will be delivered into the sub-cooler by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…5 and 6), and the possibility of freeze-out of LN emerges as a crucial design issue [10,11]. Yoshida et al presented two design ideas to avoid the freeze-out of LN flow, including a tube-in-bath type HX and a two-stage type of plate-fin HX [10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 and 6), and the possibility of freeze-out of LN emerges as a crucial design issue [10,11]. Yoshida et al presented two design ideas to avoid the freeze-out of LN flow, including a tube-in-bath type HX and a two-stage type of plate-fin HX [10].…”
Section: Resultsmentioning
confidence: 99%
“…5 and 6), and the possibility of freeze-out of LN emerges as a crucial design issue [10,11]. Yoshida et al presented two design ideas to avoid the freeze-out of LN flow, including a tube-in-bath type HX and a two-stage type of plate-fin HX [10]. Chang et al experimentally demonstrated that cross-flow heat exchangers are effective in avoiding the complete clog-up of all passages, mainly because the temperature distribution is two-dimensional [11].…”
Section: Resultsmentioning
confidence: 99%
“…The design of the sub-cooled LN heat exchanger is also ongoing [8]. In 2012, it will be demonstrated that the cooling system can cool the practical HTS transformer.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 shows a conceptual flow diagram of our cooling system, and a photograph of the refrigerator is shown in Figure 2. The refrigerator consists of a turbo-expander, a two-stage turbo-compressor, a main heat exchanger and a sub-cooler [10]. Specifications of the turbo-expander and the turbo-compressor are shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…In order to prevent LN from freezing, a newly designed sub-cooler based on a plate-fin type was made [10]. The refrigerator performance was first checked, and LN circulation system performance was also checked.…”
Section: Introductionmentioning
confidence: 99%